Challenging Divisions Through Teacher Education and History Teaching: The Case of Bosnia and Herzegovina - Larisa Kasumagić-Kafedžić; Lejla Mulalić (Center for Educational Policy Studies Journal)
Educating teachers to teach language, culture and history in a post-conflict country such as Bosnia and Herzegovina, which is still deeply divided and fragmented, implies enormous social and moral responsibilities. These endeavours represent continuous challenges where the processes of healing the wounds in such vulnerable situations, so deep and irreparable, are discussed and contextualised within the long-term social recovery in which the education of children and young people takes on a primary transformative role. The present paper examines the education policies and divisions in Bosnia and Herzegovina in the past twenty years, which reflect the segregation, politicisation and fragmentation in the post-war society. It also focuses on the role of educators in teaching for peace, antidiscrimination and intercultural understanding by addressing the issues of social exclusion, injustice, prejudice, privilege and violence across the curriculum. It problematises the construction and representation of historical and cultural knowledge, which is usually ethnocentric in orientation. Special emphasis is placed on the role of universities, i.e., university teachers and teacher educators, in promoting critical thinking and universal humanistic values among students in Bosnia and Herzegovina in general, and those studying at the English Department, University of Sarajevo, in particular. Drawing on the theories and resources of critical and intercultural pedagogy and peace education, the paper explores the possibilities of discussing stereotypes and prejudice with first-year BA students at the English Department within their Introduction to British Studies course, and with MA student teachers within their Interculturalism in Language Education course, which deals with peacebuilding and intercultural sensitivity in teaching English from a cultural perspective.